TRACING GRADUATES TO ASCERTAIN CURRICULUM RELEVANCE - Awang Ngah, Zainab; Edzan, N.N.; Abdul Rahman, Siti Suzana (Malaysian Journal of Library and Information Science, 2004)
This paper describes the study of 26 past graduates of the Master of Library and Information Science (MLIS), at the University of Malaya in order to find out the relevance of the content of the MLIS programme as well as the degree of satisfaction graduates feel about the programme. Description focuses on graduates’ (a) place of work; (b) work history; (c) work descriptions and responsibilities; (d) level of satisfaction with the programme undertaken at the Faculty; and (e) the perceived relevance of courses undertaken in the programme to their current work place. Graduates job history falls into four categorie: those who used the MLIS degree to obtain their first job; those who continue to work in the government sector after graduation; those who continue to work in the private sector and those who switch sectors after graduation. Graduates worked in a variety of posts drawing salaries of between RM1000 to RM4000 per month. Those who worked in library and information related work describe their job as developing collections, administration, preparing bibliographies, cataloguing, managing loans, readers services, library education and automation. Those who work in other areas indicated that the MLIS programme has made them more able in finding and locating needed information. Graduates are satisfied with the courses in the MLIS programme especially in the more practical oriented courses such as Organisation of Information, Information Sources and Services, Information Retrieval, and Computer Applications in Library and Information Systems. Graduates indicate their perceived usefulness of information science related courses.